Limitations of the Incorporation of Gender Perspective in Archaeological Museums: the Case of Dr. Román Piña Chan Archaeological Museum, Mexico - Muñoz Aréyzaga, Eréndira (2025)
The gender perspective is important to build an inclusive dimension in archaeological museums because it visibilizes the contribution of women to the history and development of societies, and could have an impact on cultural change. However, museums of this type in Mexico apply it in a very limited way or do not apply it at all due to conditions that need to be known. A case study was carried out in an archaeological site museum to learn, through an anthropological approach, the way in which museum professionals conceive the gender perspective and, if applicable, if it is implemented in the curatorial processes. Likewise, it was established how it is expressed in the permanent exhibitions based on an analysis of the written and visual discourses related to the feminine and the masculine. The results show that the museum does not apply the gender perspective and the exhibits present an androcentric bias.